Genetic parameters, initial growth and fruit production of dipteryx alata vogel in progeny and spacing trial - De Andrade, Henrique Sverzut Freire; De Resende Baroni, Gabriel; Brancalion, Pedro Henrique Santin; De Moraes, Mario Luiz Teixeira [UNESP]; Da Silva, Paulo Henrique Müller (Instituto de Pesquisa e Estudos Florestais (IPEF), 2020)
The tree species Dipteryx alata Vogel, known as baru, occurs naturally in the Cerrado. Its wood is valued at sawmills and the fruits have nuts that are valued for consumption in natura and industrialized. To reduce exploitation in natural populations studies are needed for genetic improvement and cultivation of the species. The objectives were to estimate genetic parameters, verify the effect of progenies and spacing on growth and fruit yield 30 months after planting. The test was implanted in the municipality of Rosário Oeste, MT with 28 progenies of open pollination in eight spacings (4.25 to 12.75m2 pl-1) in linear Nelder. The design was in a randomized block with three replications and the plots subdivided into eight spacings. Plant height, diameter at breast height (DAP) and fruit presence (PF) data were collected. Of these traits, the genetic parameters were estimated with the Selegen software using model 111 and 54. There was no effect of the spacing on the growth and presence of fruits until the evaluated age. However, there was a significant effect of progenies on the two growth traits and on the presence of fruits. For height, DAP and PF, respectively, the values of: Additive heritability were 0.38; 0.32; 0.25; coefficient of genetic variation were 11.88%; 11.53%; 11.26%; coefficient of variation were of 26.30%; 23.79%; 21.93%; coefficient of variation were 0.54; 0.48; 0.43; the mean was 3.05m; 3.43cm; 10.41%. Although no spacing effect occurs, it is expected that there will be effect at later ages. There was genetic variability between the tested progenies and strong genetic control of the characters, so there is potential for continuity of the breeding program of the species.
Parâmetros genéticos de crescimento inicial e frutificação de Dipteryx alata Vogel em teste de progênie e espaçamento
Keywords: Baru; Cerrado; Genetic improvement; Linear Nelder; Silviculture of native species